COLLABORATIVE GOVERNANCE STRATEGY IN INTEGRATED LICENSING SYSTEM ON THE AUTHORITY TO REVOKE MINING BUSINESS LICENSES FROM THE MINISTRY OF ENERGY AND MINERAL RESOURCES TO THE INVESTMENT COORDINATING BOARD - Sindy Atul Mubarokah; Edy Sutrisno (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
There are several problems with this collaboration: First, BKPM's authority is obtained through the Peraturan Menteri Energi dan Sumberdaya Mineral Nomor 19 Tahun 2020 concerning Amendments to the Peraturan Menteri Energi dan Sumberdaya Mineral Nomor 25 Tahun 2015 concerning Delegation of Authority to Grant Licensing in the Mineral and Coal Mining Sector in the Framework of Implementing Integrated One-Stop Services to the Head of BKPM (the Permen ESDM 19/2020) which was then emphasized by the Keputusan Presiden Nomor 1 Tahun 2022 concerning the Investment Task Force, but there is a problem that the granting of the delegation is not in accordance with the Government Administration Law. Second, the collaboration policy between KESDM and BKPM is not quite right if based on the Collaborative Governance theory proposed by Ansell and Gass, namely four variables consisting of initial conditions, institutional design, facilitative leadership and collaboration processes, from the data that the author found many companies that owned mining business permits (IUP) that were revoked by BKPM filed lawsuits at the State Administrative Court and the main topic of the lawsuit was the issue of BKPM's authority in the revocation. This study uses a qualitative descriptive method of analysis in the form of Ansell and Gass's theory of government collaboration, a review of government authority, and aspects of mining licensing. The conclusion of this study is that the Collaborative Governance policy between KESDM and BKPM is ineffective because there is a conflict of norms, and the strategy for effective collaboration is to obtain the basis for policy determination and an in- depth study of the philosophical, sociological, and empirical aspects.